Pengaruh Organizational Culture dan Strategic Orientation Terhadap Organizational Performance Pelaku Usaha Mikro Kecil dan Menengah (UMKM) yang Dimediasi oleh Innovation Capability - Rasyid, Muhammad Irfan; Mualim , Ahdi; Anggiani, Sarfilianti (JUDICIOUS, 2023)
The aim of this research is to look at the growth and development of Micro, Small and Medium Enterprises to be able to help and improve the economy and absorb as many workers as possible as well as the introduction of superior regional products, especially Micro and Medium Enterprises. The analysis method is carried out through explanatory research, with the PLS/SEM application. The concepts and problems studied look at causal relationships, then explain the variables that cause the problems studied. The findings from this research show the influence of organizational culture, strategic orientation, on organizational performance. There is an influence of organizational culture, strategic orientation on innovation capability. There is an influence of innovation capability on organizational performance. There is an influence of organizational culture, strategic orientation on organizational performance which is mediated by innovation capability. The theoretical implication is that innovation capability through increasing its dimensions can improve the organizational performance of Micro and Medium Enterprises and can increase the trust and loyalty of related parties. Improve and develop production quality first, paying attention to development and innovation. Strategic orientation will provide a good indication of the organizational performance of Micro and Medium Enterprises. The managerial implication states that product quality, in the process of organizational performance involvement of all entrepreneurs with third parties is very close, so that cooperation and conformity with technical specifications to the wishes of the community must be a top priority. The quality of Micro and Medium Enterprises in terms of cooperation, production quality, performance of departments such as decision makers, is a picture that can be felt by the community or collaborating parties, so these various qualities must be a priority for improving Micro, Small and Medium Enterprises.